MENGEMBANGKAN PEMBELAJARAN IPS DALAM PERSPEKTIF PARADIGMA KONSTRUKTIVISTIK (Upaya Implementatif Kebijakan Kurikulum 2013 pada Sekolah Dasar) - Senen, Anwar (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2014)
Based on the research results, Elementary School Teachers still emphasized on cognitive and psychomotor domain in social education learning. Therefore, the learning achievement of Social Education was still meaningless in students’ real life. In Law No. 20/2003 explained that the aims of national education were: to make students creative, autonomous, democratic, and responsible. To develop social education material became more meaningful, teachers needed to implement constructivistic paradigm